Persepsi Pembimbing Tentang Kurikulum Muatan Lokal Keagamaan Islam Terhadap Kenakalan Remaja Di Kabupaten Jombang - Avi Izzana; Iva Yulianti Umdatul Izzah (Universitas Lambung Mangkurat, 2026)
This study aims to analyze the perceptions of Islamic Religious Local Content (Mulok) instructors regarding the role of the curriculum as an instrument for character building and combating juvenile delinquency in Jombang Regency, “Kota Santri.” Using a qualitative approach through in-depth interviews with four junior high school instructors, this study reveals their views, experiences, and obstacles in implementing the curriculum. The results show that the Islamic Religious Local Content curriculum is considered relevant as a moral foundation for students and effective in fostering religious behavior, discipline, and responsibility. However, counselors face challenges such as time constraints, differences in student understanding, and adaptation to the digital era. Nevertheless, this curriculum has a positive impact, with a decrease in negative behaviors such as bullying and an increase in cooperation between counselors and guidance counselors. Overall, adjustments to the material, methods, and environmental support are needed to make its implementation more effective and sustainable.